Claude Pierre Molard (1759-1837) Un technicien dans la cité - Hilaire-Pérez, Liliane; Jarrige, François (Annales littéraires, 2022)
Claude-Pierre Molard is a key figure in technology at the turn of the 18th and 19th centuries. He was the first administrator of the Conservatoire des arts et métiers. To date, there has been no in-depth study of his career, from his native Jura to the École d'artillerie de La Fère, nor of his many functions, since he participated in all the technological institutions created since the end of the Ancien Régime. But more than a technologist, Molard was a practitioner and promoter of technology at a time when the idea of progress was a subject of political and social interest. Through this synthesis, an incarnate history of technical policies is proposed.